The Chemotherapy Use and Adverse Effects of Patients with Lung Cancer at Regional General Hospital in Surabaya, Indonesia - Yulia, Rika; Kirtishanti, Aguslina; Wijono, Heru; Setiawan, Eko; Presley, Bobby; Go, Tjie Kok; Mayani, Ni Putu Irma; Febriani, Anna; Jaya, Halim Priyahau; Herawati, Fauna (Pharmaceutical Sciences and Research, 2026)
In Indonesia, lung cancer is the leading cause of death related to cancer, according to Global Cancer Observatory. Chemotherapy is the most common treatment since it works systemically and can prevent cancer cells from spreading to other organs. Cytotoxicity of chemotherapy can also put patients at high risk of experiencing adverse effects. This study aimed to evaluate the congruity of chemotherapy use with treatment recommendations and the profile of adverse effects, not only acute but also delayed adverse drug reactions. This prospective observational study involved 41 adult patients with lung cancer who received chemotherapy. Data is collected through patients’ medical records, brief patient interviews, and analyzed descriptively. The majority of the patients received first-line chemotherapy (87.80%). Pemetrexed-cisplatin (39.02%) and pemetrexed-carboplatin (19.51%) are the most common first-line therapy, followed by docetaxel (12,20%) as the second-line chemotherapy commonly used by patients. The chemotherapy regimens used in patients were 100% appropriate based on treatment guidelines. 61.11% and 60% of patients experience adverse effects with the first and second line of chemotherapy, respectively. Anemia (63,89%) was the most common delayed adverse effect in the first-line chemotherapy and hair loss (60%) was the most common one in the second-line chemotherapy. The platinum-based chemotherapy is a standard treatment for lung cancer, but its tolerability limits its uses. These findings showed chemotherapy-related adverse effects that need to be considered in choosing the best choice of therapy to optimize the treatment. Therefore, prophylaxis therapy to manage chemotherapy-related adverse effects may be considered in patients with chemotherapy.